Graphene, conducting polymer and their composites as transparent and current spreading electrode in GaN solar cells. (April 2016) - Mahala, Pramila; Kumar, Ajay; Nayak, Sasmita; Behura, Sanjay; Dhanavantri, Chenna; Jani, Omkar
Abstract: Understanding the physics of charge carrier transport at graphene/p-GaN interface is critical for achieving efficient device functionality. Currently, the graphene/p-GaN interface is being explored as light emitting diodes, however this interface can be probed as a potential photovoltaic cell. We report the intimate interfacing of mechanically exfoliated graphene (EG), conducting polymer (PEDOT:PSS) and composite of reduced graphene oxide (rGO) and PEDOT:PSS with a wide band gap p-GaN layer. To explore their potential in energy harvesting, three heterojunction devices such as: (i) EG/p-GaN/sapphire, (ii) PEDOT:PSS/p-GaN/sapphire and (iii) PEDOT:PSS(rGO)/p-GaN/sapphire are designed and their photovoltaic characteristics are examined. It is interesting to observe that the EG/p-GaN/sapphire solar cell exhibits high open-circuit voltage of 0.545 V with low ideality factor and reverse saturation current. However, improved short circuit current density (13.7 mA/cm 2 ) is noticed for PEDOT:PSS/p-GaN/sapphire solar cell because of enhanced conductivity accompanied by high transmittance for PEDOT:PSS. Further, the low series resistance for PEDOT:PSS(rGO)/p-GaN/sapphire is observed suggesting that the PEDOT:PSS and rGO composite is well dispersed and exhibits low interfacial resistances with p-GaN. The present investigation leverages the potential of graphene, conducting polymer and their composites as dual capability of (a) transparent and current spreading electrode and (b) an active top layer to make an intimate contact with wide bandgap p-type GaN for possible prospect towards high performance diodes, switches and solar cells. Highlights: Heterojunction of graphene/p-GaN is fabricated and thoroughly analyzed. Graphene's opto-electrical properties leveraged for intimate contact with p-GaN. Graphene, PEDOT:PSS and PEDOT:PSS(rGO) as transparent current spreading electrode. Graphene, PEDOT:PSS and PEDOT:PSS(rGO) as active top layer for solar cells.